Manajemen Asuhan Kebidanan Pada Ny. D Masa Nifas Fisiologis dengan ASI Sedikit di PMB Ny BD. Riyanti, STR.Keb Bangetayu Kulon Genuk Kota Semarang Provinsi Jawa Tengah Tahun 2024 - Tia Widianti; Febriana Sari; Riyanti Riyanti; Sonia Novita Sari; Juliana Munthe (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
The postpartum period is the period a woman goes through, starting after giving birth to the products of conception (baby and placenta) and ending up to 6 weeks after giving birth. During the postpartum period, the reproductive organs will slowly experience changes to the state before pregnancy. This change in the reproductive organs is called involution. Postpartum care is needed during this period because it is a critical period for both mother and baby. It is estimated that 60% of maternal deaths due to pregnancy occur after delivery and 50% of postpartum deaths occur within the first 24 hours. Postpartum care is carried out to reduce maternal mortality because the postpartum period is a critical period that needs monitoring. Results: Management of Midwifery Care for Mrs. D Physiological postpartum period with little breast milk, during monitoring no potential problems were found such as signs of mastitis, blocked breast milk, breast abscess and breast cancer. However, a little breast milk comes out because there is no stimulation by the way the baby breastfeeds the mother. Conclusion: From the case study after monitoring and analyzing data on mothers with complaints of little breast milk coming out at PMB Bd. Riyanti in 2024 monitoring of the postpartum period is running normally, vital signs are within normal limits and documentation and actions have been carried out on NY "D" with the result that no gaps were found between the theory and the cases obtained.